2004
DOI: 10.1021/jm030565g
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Potent Retinoid X Receptor α Agonists

Abstract: A series of tetrahydrobenzofuranyl and tetrahydrobenzothienyl propenoic acids that showed potent agonist activity against RXRalpha were synthesized via a structure-based design approach. Among the compounds studied, 46a,b showed not only very good potency against RXRalpha (K(i) = 6 nM) but was also found to be greater than 167-fold selective vs RARalpha (K(i) > 1000 nM). This compound profiled out as a full agonist in a cell-based transient transfection assay (EC(50) = 3 nM). The two antipodes were separated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…It is notable that TLX contains a ligand-dependent C-terminal activation function 2 (AF-2) domain but not a ligand-independent N-terminal activation function 1 (AF-1) domain, which is found in many NR family members [18]. In order to explore the ligand-binding potential of TLX, Benod et al recently developed three homology models for the TLX LBD in a transcriptionally-active conformation using a chimera LBD template based on the crystal structures of two human NRs, COUP-TFII (COUP transcription factor II) and RXRa (retinoid X receptor a) [18][19][20]. This study confirmed that the TLX LBD structure resembles other NR LBD conformations as a canonical helical sandwich, and also revealed notable differences, in that the TLX LBD lacks the first helices a1 and a2 and contains a unique 5-amino-acid insertion between helices a8 and a9.…”
Section: Protein Structure Of Tlxmentioning
confidence: 99%
“…It is notable that TLX contains a ligand-dependent C-terminal activation function 2 (AF-2) domain but not a ligand-independent N-terminal activation function 1 (AF-1) domain, which is found in many NR family members [18]. In order to explore the ligand-binding potential of TLX, Benod et al recently developed three homology models for the TLX LBD in a transcriptionally-active conformation using a chimera LBD template based on the crystal structures of two human NRs, COUP-TFII (COUP transcription factor II) and RXRa (retinoid X receptor a) [18][19][20]. This study confirmed that the TLX LBD structure resembles other NR LBD conformations as a canonical helical sandwich, and also revealed notable differences, in that the TLX LBD lacks the first helices a1 and a2 and contains a unique 5-amino-acid insertion between helices a8 and a9.…”
Section: Protein Structure Of Tlxmentioning
confidence: 99%
“…While rexinoids can mimic some of the ligand-dependent actions of their partners (e.g. PPARγ agonists pioglitazone and rosiglitazone) by increasing insulin sensitivity, they suppress the actions of thyroid hormone, increase triglycerides and decrease, rather than increase, body and fat mass (Mukherjee et al 1997;Liu et al 2002;Ferre 2004;Haffner et al 2004;Ogilvie et al 2004;Li et al 2005). For example, treatment with the PPARγ-agonist, rosiglitazone, downregulated TNFα and upregulated GLUT4, MCP-1, SCD1 and CD36, while the rexinoid LG268 increased TNFα and had no effect or suppressed other genes in mouse (Singh Ahuja et al 2001).…”
Section: Rxrsmentioning
confidence: 99%
“…In other reports, db/db mice respond to a variety of RXR angonist with lowering of serum triglyceride level while rats routinely respond with elevations (12, 28 -30). Interestingly, in Haffner et al (30), male ZDF rat showed elevations in triglyceride levels at the lower RXR agonist doses with decreasing effects at higher doses while glycemia was improved in a dose-response manner. In our study, db/db mice showed a small, but consistent elevation in serum and liver triglyceride.…”
Section: Discussionmentioning
confidence: 95%